2019
DOI: 10.3906/sag-1903-188
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atrial fibrillation predictors in patients with acute coronary syndrome using ticagrelor or clopidogrel

Abstract: Background/aim: Ticagrelor is a drug widely used in patients with acute coronary syndromes (ACS) that specifically increases the plasma level of adenosine, which is likely to cause atrial fibrillation (AF). Therefore, in this study we aimed to investigate the electrocardiographic and echocardiographic predictors of AF development after P2Y12 receptor antagonists in ACS patients. Materials and methods:This cross-sectional study included 831 patients with ACS (486 [58.5%] with ST elevated myocardial infarction [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Ticagrelor could increase the adenosine half-life and plasma concentration levels and enhance the biological effects of adenosine, which has the potential to cause atrial fibrillation (Akkaif et al, 2021). However, a cross-sectional study did not find any difference in detailed ECG and echocardiographic parameters as atrial fibrillation predictors between ticagrelor and clopidogrel groups in ACS patients (Algül et al, 2019). Therefore, it is necessary to be aware that bradycardia may be related to the use of ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…Ticagrelor could increase the adenosine half-life and plasma concentration levels and enhance the biological effects of adenosine, which has the potential to cause atrial fibrillation (Akkaif et al, 2021). However, a cross-sectional study did not find any difference in detailed ECG and echocardiographic parameters as atrial fibrillation predictors between ticagrelor and clopidogrel groups in ACS patients (Algül et al, 2019). Therefore, it is necessary to be aware that bradycardia may be related to the use of ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that the incidence of PAF was significantly higher in patients with greater MBPS values, especially over 28.6 mmHg. There are numerous studies which investigate the predictors of AF development [ 25 , 26 ]. Domenech et al reported that there was a significant relationship between nighttime BP and left atrial size and speculated that nighttime BP levels, but not office BP levels, play the most important role in left atrial remodeling and enlargement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On multiple regression analysis, LDL, mitral regurgitation, LA dyssynchrony, Inter-atrial dyssynchrony and LAVI max were significant predictors for AF development (P value =0.046, 0.022, <0.001, <0.001, 0.008 respectively). (4) . In terms of ECG data, P-max, P-min, PWD, PR interval, P wave axis, were insignificantly different between the studied groups (P-value > 0.05).…”
Section: A) B)mentioning
confidence: 99%
“…These differences led to the hypothesis that ticagrelor has pleiotropic properties and nonplatelet directed mechanisms of action. These effects of ticagrelor have been mostly attributed to increased halflife and plasma concentration of adenosine (4) . Adenosine is a purine nucleoside primarily produced by endothelial cells.…”
Section: Introductionmentioning
confidence: 99%